A Study Regarding the Basic Anatomy and Physiology of the Eye among Nursing Students: A Cross-Sectional Study: Studi Mengenai Anatomi dan Fisiologi Dasar Mata di Kalangan Mahasiswa Keperawatan: Sebuah Studi Cross-Sectional - Hamid, Samahir Sabri; Kareem, Afkar Fadhil; Tiryag, Ali Malik; Abdul-Ra’aoof, Husham Hussain (Universitas Muhammadiyah Sidoarjo, 2025)
Objective: to determine the correlation between students' demographic information (age, sex, and stage) and their knowledge of the anatomy and physiology of the eye. Methods: A cross-sectional study was conducted at the College of Nursing at the Bab Al-Zubair Campus in Al-Basrah City. Nursing students are a sample of the study (100), and purposive (non-probability) sampling. The period of the study extended from the 12th of May 2024 to the 10th of February 2025. The questionnaire was constructed by the researchers on reliability (Cronbach’s alpha) for 32 items (0.81) and validity of the questionnaire by 13 experts in the field. Results: The findings of these results indicate that most students (60%) have moderate knowledge about the anatomy and physiology of the eye, and (40%) have good knowledge. Conclusion: The results of the study show that most students only have a moderate knowledge of the anatomy and physiology of the eye Highlights: Assess link between demographics and eye anatomy knowledge. Cross-sectional study using questionnaire with 100 nursing students. Most students had moderate understanding of eye anatomy.. Keywords: Nursing, Students, Anatomy, Physiology, Eye